Impact of Disruptive Technologies on the Sharing Economy - Gaol, Ford Lumban (IGI Global, 2019)
Because it continually implements entrepreneurial creativity and innovative business models, the economic landscape is ever-changing in today's globalized world. As consumers become more willing to accept new strategic trends, this has led to the emergence of disruptive technologies. Since this equipment has an insufficient amount of information and high risks, it is necessary to assess the potential of disruptive technologies in the commercial environment. Impact of Disruptive Technologies on the Sharing Economy provides emerging research exploring the theoretical and practical aspects of dis.